Justice and Leader-Member Exchange: The Moderating Role of Organizational Culture - Erdogan, Berrin; Liden, Robert C.; Kraimer, Maria L. (Academy of Management Journal, 2006)
We hypothesized that organizational culture moderates the relationship between justice perceptions and leader-member exchange (LMX). In a sample of 516 teachers from 30 high schools in Turkey, we found that one dimension of culture from the Organizational Culture Profile, respect for people, strengthened the relationship between interactional justice and LMX, and another dimension, team orientation, weakened that relationship. Furthermore, aggressiveness strengthened, whereas team orientation weakened, the relationship between distributive justice and LMX. Finally, we found that in team-oriented schools, LMX was higher.